THU0568 Biosimilar use in patients with juvenile idiopathic arthritis in a real-world setting in the united kingdom. (12th June 2018) - De Cock, D.; Kearsley-Fleet, L.; Davies, R.; Baildam, E.; Beresford, M.; Foster, H.; Southwood, T.; Thomson, W.; Hyrich, K.; ,
Abstract : Background: Although biosimilars are routinely used in adults with musculoskeletal diseases, there are limited data regarding the use of biosimilars in patients with juvenile idiopathic arthritis(JIA). Objectives: To describe the characteristics of patients with JIA starting biosimilars in the United Kingdom (UK) following their approval in the UK with musculoskeletal diseases. Methods: Patients were selected from the Biologics for Children with Rheumatic Diseases (BCRD) study, launched in 2010, an ongoing prospective UK study of biologic therapies other than the etanercept originator (followed in a separate parallel study) in JIA. Baseline information is collected via questionnaires completed by the treating physician or affiliated clinical research nurse. Follow-up data including disease activity measures and changes in drug therapy are collected at 6 months, 1 year and annually thereafter. From 30-Sept-2015, data has been captured on 3 biosimilars available in the UK: 2 infliximab and 1 etanercept biosimilar. Results: To 12-Dec-2017, 58 patients were identified in the BCRD study starting a biosimilar; 48 (84%) infliximab and 10(17%) etanercept biosimilars (table 1). Of these, 36 (62%) started a biosimilaras their first biologic therapy. Seventeen (29%) switched to a biosimilar from a non-originator biologic. Five patients switched from their originator. Follow-up data ranging from 6 months to 2 years were available in 14 patients. Four patients switched to another biologic in this period, 3 switching from an infliximab biosimilar to tocilizumab, and 1 etanercept biosimilar patient to adalimumab. Two serious adverse events in a 90 day exposure window were reported, both cases of recurrent uveitis in patients on an infliximab biosimilar switching from a non-originator biologic. Conclusions: Biosimilars in children and young people are used as both first-line and subsequent-line biologic therapy, although currently few UK children have been switched directly from an originator product. Whether a move towards switching all children receiving originator products to biosimilar products, as has been seen in rheumatoid arthritis, will occur is currently unknown but it is imperative that the safety of these treatment decisions are captured in patient registers. Disclosure of Interest: None declared